Substituição tributária, neutralidade e direitos fundamentais do contribuinte - Rebouças, Bruno Nogueira (2024)
This work is dedicated to an analysis of limitations imposed by our constitutional system on the so-called legal regime of indirect passive subjection in the form of tax substitution responsibility, a practice now commonly adopted in our domestic law, as evidenced in the tax legislation of various federated entities. The aim is to reveal some incongruities when it comes to its legal imposition and to identify what we term as systemic distortions in the adoption of this specific responsibility regime. All of this is carried out through a critical analysis of the jurisprudence of the Superior Courts, notably the Supreme Federal Court, which had the opportunity to directly address the issue or, at the very least, managed to touch upon the core of several discussions linked to the central theme explored throughout this work